1973
DOI: 10.1038/bjc.1973.169
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanisms of Action of the Carcinogenic Nitroso and Related Compounds

Abstract: It is suggested that the proximate carcinogenic forms of dialkylnitrosamines are their oxidation products, which retain the alkylnitrosamino moiety, but have acquired a carbonyl function as a result of omega or beta oxidation of an alkyl group. Such metabolites resemble the locally acting carcinogenic “nitrosamides” and probably have become multifunctional. Their functional groups, being in close proximity, could ensure binding in a concerted manner with apposite reactive centres of chromatin to form a firm br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
3

Year Published

1975
1975
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(14 citation statements)
references
References 10 publications
1
10
0
3
Order By: Relevance
“…The fact that in some animal studies 1.2-dimethylhydrazine-orazoxymethane-induced carcinogenesis was en hanced by chronic ethanol feeding in the left bowel [19] or in the rectum only [13] could be due to the fact that an increased production of the ultimate carcinogen dimethyl ion by the metabolism of the procarcinogens via an enhanced activity of ADH in this segment occurs. Indeed, it has been reported that the incidence of methylazoxymethanol-induced intestinal tumors is paralleled by the ac tivity of intestinal mucosal ADH [21],…”
Section: Discussionmentioning
confidence: 99%
“…The fact that in some animal studies 1.2-dimethylhydrazine-orazoxymethane-induced carcinogenesis was en hanced by chronic ethanol feeding in the left bowel [19] or in the rectum only [13] could be due to the fact that an increased production of the ultimate carcinogen dimethyl ion by the metabolism of the procarcinogens via an enhanced activity of ADH in this segment occurs. Indeed, it has been reported that the incidence of methylazoxymethanol-induced intestinal tumors is paralleled by the ac tivity of intestinal mucosal ADH [21],…”
Section: Discussionmentioning
confidence: 99%
“…The plant, commonly know as 'Yaa Nguang Chaang' in Thai, belongs to the family Boraginaceae and is used as a traditional medicine in many countries, [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] including Thailand, where it has been used as an asthma treatment and as a diuretic. 9 Several studies on the chemical constituents and biological activities of the crude extract from H. indicum have been reported, [17][18][19][20][21][22][23][24][25][26][27][28][29] but the components and biological activities of H. indicum essential oil have not been studied previously. We report here the results of the identification of H. indicum essential oil components using gas chromatography (GC-FID) as well as GC-MS analysis and its antituberculosis activity.…”
Section: Introductionmentioning
confidence: 99%
“…56,57 The first hint came in the early 1960s from Norway, when sheep died of liver toxicity after feeding nitrite-preserved herring meal. 57,58 The effect of nitrate, nitrite, and NOCs on human health has been a recurrent issue with respect to cancer [59][60][61][62] due to unawareness of the general population exposure to NOCs, namely, diethylnitrosamine (DEN), present in foods, beverages, tobacco smoke, 57,[63][64][65] drinking water, and industrial pollution. 66,67 Endogenous synthesis of NOCs are also mentioned for being responsible for 45%-75% of total exposure.…”
Section: Experimentally Induced Liver Tumorsmentioning
confidence: 99%